2020
DOI: 10.1038/s41598-020-75815-x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic rhinosinusitis and premorbid autoimmune diseases: a population-based case–control study

Abstract: Evidence shows that chronic rhinosinusitis (CRS) is associated with prior presence of autoimmune diseases; however, large-scale population-based studies in the literature are limited. We conducted a population-based case–control study investigating the association between CRS and premorbid autoimmune diseases by using the National Health Insurance Research Database in Taiwan. The CRS group included adult patients newly diagnosed with CRS between 2001 and 2013. The date of diagnosis was defined as the index dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Many studies have investigated the association between autoimmune diseases and CRS, because autoimmune diseases are thought to share the same or similar pathogenic mechanisms as those relevant to the development of CRS. In addition, autoimmune disease may contribute to a poor CRS prognosis [ 11 ]. Shih et al previously reported that CRS was statistically significantly associated with autoimmune diseases in a Taiwanese population-based case–control study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have investigated the association between autoimmune diseases and CRS, because autoimmune diseases are thought to share the same or similar pathogenic mechanisms as those relevant to the development of CRS. In addition, autoimmune disease may contribute to a poor CRS prognosis [ 11 ]. Shih et al previously reported that CRS was statistically significantly associated with autoimmune diseases in a Taiwanese population-based case–control study.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported an association between CRS and autoimmune diseases such as psoriasis, lupus, rheumatoid arthritis, multiple sclerosis, and ankylosing spondylitis. A recent population-based study revealed that CRS was statistically significantly associated with premorbid autoimmune diseases [ 11 ]. Additionally, Fallahi et al revealed that autoimmune thyroiditis is associated with a range of autoimmune diseases, such as chronic autoimmune gastritis, vitiligo, rheumatoid arthritis, multiple sclerosis, Sjögren’s disease, and systemic lupus erythematosus [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Shih et al showed that chronic rhinosinusitis (CRS), with and without nasal polyps, demonstrated a significant association with premorbid autoimmune diseases (i.e., ankylosing spondylitis, polymyositis, psoriasis, rheumatoid arthritis, sicca syndrome, and systemic lupus erythematosus). However, the literature on the subject is sparse [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory and infectious upper respiratory diseases (IURD) affect the sinonasal tract, pharynx, and larynx, and include diseases such as chronic tonsillitis, allergic rhinitis, and chronic rhinosinusitis. They lead to increased morbidity 1,2 and costs 3 , and to the highest public health burden in the world by serving as the main route of infection to the body, and by their connection to non-communicable diseases, such as asthma [5][6][7] , autoimmune diseases 8,9 , cardiovascular diseases 10 and obesity 11 . Genetic predisposition [12][13][14][15] together with environmental megatrends such as the COVID-19 pandemic [16][17][18] , Western lifestyle 19 , urbanization 20,21 , global warming 22 and dysbiosis 23,24 influence the burden of IURDs.…”
Section: Introductionmentioning
confidence: 99%